Crotalaria madurensis flavonol glycosides’ antibacterial activity against Staphylococcus aureus - Hala Sh. Mohammed; Salwa A. Abu El Wafa; Mona H. Ibrahim; Rasha Mohammad Fathy; Noha A. Seif-Eldein (AMB Express)
Abstract Methicillin-resistant Staphylococcus aureus (MRSA) infections are prevalent in hospitals and often lead to significant health complications. This study aimed to explore the chemical composition of the aerial part of Crotalaria madurensis and evaluate its antioxidant and antibacterial properties. The impact of gamma irradiation on the antibacterial properties of the plant extract and metabolite 1 against MRSA was also examined. Fourier-transform infrared (FTIR) analysis was conducted on the filtrates of untreated MRSA and MRSA treated with the plant extract and metabolite 1. Four flavonol glycosides were identified as gossypetin 8-methoxy, 3-O-β-D-xylopyranoside (metabolite 1), gossypetin 8-O-β-D-glucopyranoside (metabolite 2), kaempferol 3-O-β-D-glucpyranoside (Astragalin, metabolite 3), and herbacetin 7-methoxy-3-O-β-D-glucopyranoside (metabolite 4). All metabolites exhibited significant antioxidant properties using different assays. The antibacterial efficacy of the extract and metabolite 1, which showed substantial antioxidant properties compared to the other isolated metabolites, was evaluated. Both the plant extract and metabolite 1 significantly reduced the viability and cell count of MRSA at concentrations of 1.0 and 0.5 mg/ml. The antibacterial activity of the plant extract and metabolite 1 was assessed after gamma irradiation at 50 and 100 Gy, which did not significantly affect the antibacterial efficiency. FTIR analysis indicated that the plant extract and metabolite 1 significantly altered the band frequency values, bandwidth, and peak intensity % of the treated MRSA filtrate. Molecular docking studies suggested that metabolite 1 exhibited the highest antioxidant and anti-MRSA activity, with strong binding scores like the ligand, indicating an effective interaction and high affinity between metabolite 1 and the target molecule.